Perancangan User Experience Dengan Menggunakan Metode Human Centered Design Untuk Aplikasi Info Calon Anggota Legislatif 2019 - Yulius Firantoko; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
General elections are one of the most vital elements In democracies country, because measuring democratically a country depends on the general elections held by the country. In campaigns political parties are still enchant their support with ‘dangdut' and prizes and only a little talk about idea, their focus is to familiarize voters with party symbols and numbers on letters. At present the people are able to assess the performance of the political elite by looking at the phenomenon of corruption and abuse of power indicated by the court. But it cannot be one only fault of the organizers and the government because there is also ignorance of the people who voted without influencing the background, achievements and track record of the participants they chose. This research aims to design an application for info legislative candidates with good user experience and is expected to provide easy information about legislative candidates to the public. The method used in this research is human centered design for designing user experience and elements of user experience for the design phase. After analyzing the context of use and user needs, the solution design will be continued. Solution design evaluation uses a heuristic evaluation method that involves 3 experts as evaluators. From the evaluation results, 17 problems were listed based on the highest average severity ratings. Where one of the problems is included in a major problem which has a high priority of improvement. The results obtained from this study are the application design in the form of a prototype and design recommendations for improving the design of the application in further development.